Yevgen Tymofiyovych Skliarenko - Ukrainian association of orthopaedists-traumatologists, Staff of (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
The article deals with the 85th birthday of twice winner of the State Prize of Ukraine, Honoured Scientist of Ukraine, Doctor of Medical Science, Professor Ye.T. Skliarenko.